Influence of behavioral characteristics of people who inject drugs on uptake of harm reduction services: an observational study - Nyaga, Muthoni; Otieno, George; Yoos, Alison; Wanjau, Grace; Muli, Raphael (International Journal Of Community Medicine And Public Health, 2022)
Background: People who inject drugs (PWID) are stigmatized and discriminated against and consequently experience barriers to essential services, which limit their access to care. Without the necessary treatment and unaware of the risks associated with injecting drug use, they remain vulnerable to HIV, hepatitis B and hepatitis C infections by sharing contaminated injecting equipment. Harm reduction programs are beneficial in reducing the risk of spreading these infections; however, uptake remains low at less than 20-40% in Sub-Saharan Africa. The study sought to assess the influence of behavioral characteristics of PWID on uptake of harm reduction services in Nairobi City County, Kenya. Methods: A cross-sectional study design was adopted using respondent-driven sampling to recruit participants in the study. Descriptive and bivariate analyses were carried out. One hundred ninety-two respondents participated in the study, 126 (66%) male and 66 (34%) female. About 71.35% of respondents had low uptake, and 28.65% had high uptake of harm reduction services. The relationship between period of injecting and uptake of harm reduction services was statistically significant at X2=7.079, p value 0.029. Results: PWID injecting on a less frequent basis were significantly more likely to have adopted harm reduction practices. Peer group support, as well as support from family, were also statistically significant at X2=7.87, p=0.005 and X2=21.869, p<0.001 respectively. These findings suggest that support from peers or family is likely to increase their probability of adopting harm reduction services. Conclusions: In summary, advocacy, peer support groups and social support networks are encouraged for harm reduction. A study on other factors influencing uptake of harm reduction services may be considered based on the health belief model or the socio-ecological model.